Design of biomimetic targeting nanoclusters for enhanced doxorubicin delivery to liver cancer. (15th March 2023) - Charles Kunene, Sikhumbuzo; Lin, Kuen-Song; Weng, Meng-Tzu; Janina Carrera Espinoza, Maria; Lin, You-Sheng; Lin, Yi-Ting
Graphical abstract: Highlights: pH-responsive RGO nanoclusters were constructed through benzoic-imine bonds; Cancer CM modification presented nanoclusters with biomimetic targeting ability; PEGylation or biomimetic targeting enhanced cellular intake and therapeutic effect; High drug was released at pH 5.4, however, low drug was release under pH 7.4. RGO–DOX–PEG–CM showed higher tumor inhibition capability. Abstract: Herein, pH-sensitive nanocluster platforms were constructed by reduced graphene oxide (RGO), encapsulated with anticancer drug known as doxorubicin (DOX) via benzoic-imine covalent bonds and surface-modified with polyethylene glycol (PEG) for enhanced tumor accumulation and cancer cell membrane (CM) for homologous targeting ability. Strong characteristic diffraction bands of GO at 2θ = 26.6° indexed (002) traces of RGO were observed, demonstrating that the nanoclusters were composed of graphene species. Raman spectra, showed two strong intensity peaks in the scattering spectrum of RGO and RGONP–PEG–CM, that are the D band (1329 cm −1 ) and G band (1575 cm −1 ) corresponding to GO. The in vitro cell viability demonstrated biocompatibility and nontoxicity behavior of the nanoclusters towards HepG2 cell line with 95 % cell viability. In contrast, the DOX-loaded formulation exhibited a significant therapeutic effect. The accumulative DOX release results revealed a pH-sensitive drug release displaying a Weibull kinetics model which displayed the best fit for the studied drug delivery system. As predicted, RGONP–DOX–PEG–CM demonstrated the highest antitumor effect, with the lowest tumor sizes in vivo . Additionally, DOX-conjugated groups significantly displayed large necrotic and apoptotic areas compared to drug-free groups, and no evident inflammation was observed in the main organs. The designed RGONP–DOX–PEG–CM might be established as a multipurpose therapeutic platform for homotypic membrane-membrane recognition of numerous cancer types.